Photoinduced Multicomponent Reactions. Issue 50 (12th October 2016) - Garbarino, Silvia; Ravelli, Davide; Protti, Stefano; Basso, Andrea
Abstract: The combination of multicomponent approaches with light‐driven processes opens up new scenarios in the area of synthetic organic chemistry, where the need for sustainable, atom‐ and energy‐efficient reactions is increasingly urgent. Photoinduced multicomponent reactions are still in their infancy, but significant developments in this area are expected in the near future. Abstract : In the spotlight : Multicomponent approaches have recently been applied to light‐driven reactions with the aim of developing sustainable, atom‐ and energy‐efficient reactions. A comprehensive collection of photoinduced multicomponent reactions (MCRs) is presented in this Minireview.